Rural women and food security in Mymensingh district (Journal of the Bangladesh Agricultural University, 2014)
The study was undertaken to determine the key factors relevant to rural women enhancing food security which have great contribution to their family and community. A sample size of 80 women was drawn from Char Ishawrdia village of Mymensingh Sadar upazila. The findings showed that most of the respondents were economically active but not well educated. It was found that the yearly average income and expenditure of the households were Tk.66656.25 and Tk.67238.75 respectively. It was also found that yearly average income of the respondents was only Tk.7600.00. Rural women of the study area were involved in harvesting crops, crop production, livestock rearing, homestead forestry and gardening, post-harvest operation, cooking, cleaning house, washing clothes and caring children. It was found that women headed households food security is affected by some socioeconomic factors. In functional analysis, the Log Linear model was fitted best. Result shows that the household food security was significantly influenced by education of respondent, family size, household income, access to credit, and social participation. Women were found highly empowered in the study area and empowered women had great contribution to ensure the household food security. With the process of empowering women, women have a chance to increase their income, to participate in decision making process, to build up their health and nutritional knowledge, control over capital and participate in social and political activities through which they can easily ensure food security. Findings of the study suggest that government should provide different types of facilities to rural women which will help them to ensure households food security. Government should also take attempts to change the social attitudes towards the rural women. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21399 J. Bangladesh Agril. Univ. 12(1): 105-110, June 2014